A comparison of natural and induced diversity in plant oils☆ - Chardot Thierry (Oilseeds and fats, crops and lipids, 2022)
Currently, there is a growing demand to replace the compounds in a given product that are of a petroleum origin with renewable resources. One of these compounds, called fatty acid (FA), is the main component of vegetable oils. FA composition is not only responsible for the physicochemical properties of plant oils, but it also determines their uses. For example, since time immemorial, products containing lipids have been used for lighting and heating purposes. They are also excellent lubricants and possess drying properties important molecules for painting, and wood preservation. In terms of nutrition, they have a high-energy content, are part of our daily health requirements, and are used for animal feed. We present here some lipids of interest, the plants that produce them naturally with high yield, the enzymes responsible for their synthesis when known, and their possible uses, as well as resources and ways that could allow the lipids of interest to be produced in quantity in different hosts.